Humour in times of confrontation, 1901 to the present
1 online resource (224 pages)
Keywords: Humour in Times of Confrontation: 1901 to the Present examines the various and surprising ways in which humour has been powerfully employed, through a wider range of media than possible at any other time in history, as a response to conflict.With no earlier century undergoing more diverse, more extensive, and more intense conflicts than the period in question, the last twelve decades provide a unique landscape to explore the farthest edge of humour: its darkest side. This book argues that such conflict has not only traumatically shaped the modern psyche but created a fertile ground for humour to grow and evolve with the advent of new representations and technologies. The chapters in this volume focus on international conflicts that have been reported widely through news media but seldom regarded as material for serious humour studies. Each chapter begins by engaging with a particular form of confrontation before providing a case study of how it has contributed to the creation, enjoyment, and/or sharing of humour via different media.This volume is a valuable resource to students and scholars of humour studies, modern cultural and social history, the history of technology, and media studies.